Effects of chronic co-exposure polystyrene nanoplastics and cadmium on liver function in Prussian carp (Carassius gibelio) - Mingzhong Luo; Yilin Ding; Huixin Zeng; Yanfei Zhong; Haoyu Zhang; Yuxi Chen; Xiaoli Xu; Wei Wei (Ecotoxicology and Environmental Safety)
Nanoplastics (NPs) are tiny plastic particles that arise from the degradation of microplastics. They have an extensive presence in aquatic environments and exert high ecotoxicity in aquatic organisms. In this study, Prussian carp (Carassius gibelio) was used to assess the hepatotoxicity of polystyrene nanoplastics (PS-NPs) and cadmium (Cd) following 21 days of individual and combined exposures. The results showed that co-exposure to PS-NPs and Cd enhanced PS-NPs accumulation in the liver. Compared to their individual effects, simultaneous exposure to PS-NPs and Cd led to more severe histopathological damage to liver tissue and increased liver transaminases activities. Additionally, this co-exposure resulted in decreased superoxide dismutase (SOD) activity, with increased malondialdehyde (MDA) and total antioxidant capacity (T-AOC). Moreover, the transcriptional levels of immune-associated genes were up-regulated. In conclusion, PS-NPs and Cd exhibit synergistic toxic effects on the liver of Prussian carp. These findings offer crucial insights into the combined hepatotoxicity of NPs and heavy metals in aquatic organisms, suggesting potential risks to human health.